Associations of Building Characteristics and Lifestyle Behaviors with Allergic Disease for Adults in Shanghai: from a Cross-sectional Survey. (2017) - Sun, Chanjuan; Guo, Yuchao; Huang, Chen; Zou, Zhijun; Hu, Yu; Liu, Wei
Abstract: Few studies have illustrated the effects of residential environmental conditions on prevalence of allergic disease for adults. A cross-sectional study with 17898 valid samples from parents of preschool children was carried out during 2010-2011 in Shanghai, China. The allergic symptoms of these participants were surveyed; meanwhile the building characteristics, environmental exposures and lifestyle behaviors were all reported by the questionnaires. Pearson's Chi-square (χ2), Gamma correlation analysis and logistic regression analysis were applied to investigate associations between building characteristics, lifestyle and their allergic symptoms. The results displayed that interior renovation or adding new furniture, home dampness-related indicators and the residential distance within 200 meters of the traffic trunk or highway, using incense and so on were the significant risk factors for allergic symptoms (p<0.05, AOR>1), while exposing the bedding to sunshine is a protective factor, so we can draw that controlling indoor air pollution and the residential dampness-related indicators, as well as changing the bad habits are the effective measures to prevent allergic symptoms.